The influence of selected ionic liquids on activity of chitin deacetylase - Aspras Izabela; Kamińska Małgorzata; Karzyński Kamil; Kawka Mateusz; Jaworska Małgorzata M. (Chemical and Process Engineering)
Chitin deacetylase is the only known enzyme which is able to deacetylate N-acetyl-D-glucosamine units in chitin or chitosan chains. As chitin can hardly be dissolved in organic/inorganic solvents, new solvents are still searched. Ionic liquids are promising for that application and for homophase enzymatic deacetylation. The aim of the work was to investigate the influence of selected ionic liquids on activity of chitin deacetylase.